Documenting the Seasonal Agricultural Worker Program: A Filmed Interpretation - Graciela Martínez-Zalce (Norteamérica)
This article uses a qualitative content analysis to examine the documentary El Contrato (2003), directed by Korean-Canadian documentary filmmaker Min Sook Lee and produced by the National Film Board, from two complementary standpoints: first, the critical portrait it paints of the Seasonal Agricultural Worker Program (SAWP), a partnership of governments and agro-industrial firms, its social consequences, and the integration problems it presents; and second, the importance of documentary cinema in making visible and analyzing the conditions of temporary workers in Canada. The author concludes that this documentary’s activist strategy contributes to making integration easier.